FLVCR1 Predicts Poor Prognosis and Promotes Malignant Phenotype in Esophageal Squamous Cell Carcinoma via Upregulating CSE1L - Zhou, Suna; Zhang, Mingxin; Zhou, Chao; Meng, Yinnan; Yang, Haihua; Ye, Wenguang (Frontiers in Oncology, 2021)
Objective Dysregulation of feline leukemia virus subgroup C receptor 1(FLVCR1) expression has been investigated in several tumors. However, the expression and role of FLVCR1 in esophageal squamous cell carcinoma (ESCC) remain largely unknown. Methods FLVCR1 expression in tissues was measured by immunohistochemical staining (IHC). Celigo assay, MTT assay, colony formation, caspase 3/7 activity analysis, wound healing assay, Transwell migration, and invasion assay were applied to assess the effects of FLVCR1 on ESCC tumorigenesis. Coimmunoprecipitation (Co-IP) and liquid chromatography-mass spectrometry (LC-MS) were used to identify protein interactions with FLVCR1. An in vivo imaging system (IVIS) was used to investigate the functions of FLVCR1 on the growth and metastatic capability of ESCC cells in a xenograft model and a tail vein metastasis model. Results Elevated expression of FLVCR1 was detected in ESCC tissues and predicted poor survival. Upregulated FLVCR1 was positively correlated with lymph node metastasis (N stage) and late tumor-node-metastasis (TNM) stage. FLVCR1 knockdown inhibited cell proliferation and colony formation ability, induced cell apoptosis, and repressed cell migration and invasion of ESCC in vitro. Inhibition of FLVCR1 markedly repressed tumorigenicity and metastasis of ESCC cells in vivo. Mechanistically, chromosome segregation 1–like (CSE1L) was identified to interact with FLVCR1 using a Co-IP assay. Moreover, the inhibitory effect of FLVCR1 knockdown on proliferation and migration was counteracted by the exogenous expression of CSE1L. Conclusion FLVCR1 plays a pivotal role in ESCC cell survival, growth, and migration. These functions may be partially dependent upon the protein interaction between FLVCR1 and CSE1L. In addition, FLVCR1 can be applied as a clinical prognostic marker for patients with ESCC.